An Overview of the Family Assistance Team's Role in Stunting Prevention in an Integrated Health Post : A Case Study at Working Area of Godean Community Health Center I, Yogyakarta, Indonesia - Shelly Pradila; Astuti, Dhesi Ari; Romero, Cyril B. (Journal of Public Health Sciences, 2023)
Indonesia has Southeast Asia's second-highest child stunting rate and fifth-highest globally. Malnutrition can cause stunting, especially during the First 1000 Days of Life (HPK). This study aims to investigate the role of the family support unit in preventing stunting in a particular Integrated Service Post in Indonesia. This is a qualitative investigation. This study included 5 participants: family planning cadres, cadres, village midwives, and members with toddlers and expectant mothers. The results of the data analysis indicated the function of companion team families in preventing stunting, particularly for pregnant women and mothers with children. This demonstrates that the duties assigned are appropriate for their positions, as outlined in the Guidelines for Implementing Family Assistance in Efforts to Accelerate Stunting Reduction. The Family Support Team's function is particularly effective in decreasing stunting, especially for pregnant women and mothers with children under two years old who are at risk because stunting rates decrease with assistance. It is expected that there would be more monitoring of the improvement of each cadre's skills in carrying out their tasks and roles by the guidelines so that they can be more optimised in providing support.